Charitable Trusts As A Device For Indigenous Peoples To Merge And Develop Customary Land - Hare, C. Michael (Journal of Malaysian and Comparative Law, 2019)
Indigenous people throughout the world are struggling to survive as viable communities, preserve their culture, and attain self-determination. In Hawai’i, one historical tool that has been employed to aid the preservation of indigenous people has been charitable trusts. These trust were created by members of the Hawaiian royalty, ali’i, with the express purpose of aiding indigenous Hawaiian people. The main charitable trusts in Hawai’i are referred to as the "Ali’i Trusts" and include the Lunalilo Trust, Kamehameha Schools Bishop Estate, and Queen Lili’uokalani Trust. This paper provides an overview of the legal principles applicable to charitable trusts and then summarises the three primary charitable trusts created in Hawaii to aid native Hawaiian people.